Caracterização experimental do fenômeno de sensibilização comportamental imediata após administração única de diferentes drogas de abuso em camundongos - Alvarez, Juliana do Nascimento [UNIFESP] (2009)
The behavioral sensitization phenomenon is characterized by a progressive and enduring enhancement of the locomotor stimulant effect of drugs of abuse following repeated treatment in rodents. This behavioral phenomenon seems to share the same neurobiological basis of drug dependence in humans and has been proposed as a pathophysiological animal model of drug dependence. Recently, we demonstrated an early-onset type of behavioral sensitization. Indeed, an “induction” injection of amphetamine potentiated the locomotor stimulant effect of a challenge injection of the drug, given some hours later. The aims of this Thesis were threefold: 1-) to behaviorally and neurochemically characterize the rapid-onset type of behavioral sensitization to amphetamine in mice, 2-) to verify if the rapid-onset type of behavioral sensitization would also occur to other drugs of abuse (cocaine, morphine and ethanol) and 3-) to investigate the possible development of rapid-onset cross-sensitization between amphetamine and cocaine, morphine or ethanol. Mice´s open-field locomotor activity was used as the experimental paradigm. We verified the development of the rapid-onset type of behavioral sensitization to amphetamine in the several behavioral parameters analyzed in the open-field (locomotion, rearing and immobility), by administering 2 injections of 2,5 mg/kg amphetamine, separated by a 4h interval. We demonstrated that this phenomenon was not a consequence of the stress induced by the priming injection of amphetamine and was not due to residual levels of the drug. Moreover, greater neuronal activation in the nucleus accumbens was observed in sensitized mice, in the absence of pré-synaptic neurochemical alterations in their striatum-accumbens, suggesting that postsynaptic adaptations may be involved. The rapid-onset behavioral sensitization also developed to cocaine and morphine, but not to ethanol. Finally, rapid-onset cross-sensitization occurred between amphetamine and the other drugs of abuse in a bidirectional way, except for ethanol. Within this aspect, cross-sensitization between amphetamine and ethanol only developed when amphetamine was administered during the induction of this phenomenon and ethanol in its expression. The present results may contribute to the comprehension of the mechanism involved in the binge pattern of drug abuse.